The Effect of Financial Rewards, Job Market Considerations, Personality, Social Values, and Professional Training on Career Selection as Public Accountant - Ningrum, Wuri Wijaya; Karsiati, Karsiati (Untag Business and Accounting Review, 2022)
This study aims to obtain empirical evidence regarding the effect of financial rewards, labor market considerations, personality, social values, and professional training on career choices as public accountants by accounting students in Semarang City. The population in this study were 8th semester accounting students at the University of 17 August 1945 Semarang (UNTAG), Dian Nuswantoro University (UDINUS), and Diponegoro University (UNDIP). The sampling technique used is purposive sampling. The data used are primary data obtained by distributing questionnaires. Respondents in this study amounted to 188 people. The analytical tool used is multiple linear regression with IBM SPSS version 23. The results show that financial rewards and social values have a positive and significant effect on career choice as a public accountant. Furthermore, l labor market considerations, personality, and professional training have no effect on career choice as a public accountant.